Predictors of the Czech learners´ acquisition of selected English phonemes - Černá, Monika; Ivanová, Jaroslava; Myslivec, Jaroslav (My University, 2017)
The study investigates predictors of the acquisition of selected English phonemes in a foreign language context. University students’ pronunciation was diagnosed by two tests; their ability to produce seven selected phonemes was assessed. Furthermore, data regarding the students’ learning histories was obtained through a questionnaire. Then a multiple regression analysis was conducted in order to identify predictors of the acquisition of the selected phonemes. The analysis uncovered several factors, the most significant being pre-school exposure to English and positive attitudes to English in adolescence, which appeared to influence the subjects’ pronunciation positively. Interestingly, several factors which relate to learning English at school appeared to exert a negative influence on the acquisition of the selected phonemes. Furthermore, the study underscored the importance of metacognition in relation to autonomous learning.
Prediktory osvojení vybraných anglických fonémů u českých studentů
Keywords: English as a foreign language; pronunciation; segmental features; age factor; attitudes; gender; learning contexts; angličtina jako cizí jazyk; výslovnost; segmentální jevy; faktor věku; postoje; gender; kontexty učení